A Synergistic Effect of Free Radical Scavenging Activity of the Combination of Mangifera indica and Euphorbia hirta Extracts - Putra, I Made Wisnu Adhi; Suarjana, Nyoman; Mahfur, Mahfur; Hasnawati, Hasnawati (Indonesian Journal of Chemistry, 2025)
Due to its synergistic effect, the extract-extract combination is essential in traditional medicine formulation. The combination of Mangifera indica and Euphorbia hirta extracts can produce a synergistic effect if combined in a proper ratio. This investigation reported the synergistic antioxidant effect of M. indica and E. hirta. The ethanolic extracts of M. indica leaf (MILE) and E. hirta aerial part (EHAE) were acquired by the maceration method, followed by evaporation to remove the solvent. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) tests were used to assess the extracts' capacity to scavenge radicals. MILE and EHAE were combined with a ratio of 1:3 (comb. 1), 1:1 (comb. 2), and 3:1 (comb. 3). This work disclosed that the extract combinations showed all types of interactions. However, of all combinations, only comb. 3 depicted the synergistic interaction caused by the regeneration effect of EHAE on MILE. This finding has important implications for health, particularly disease prevention. M. indica and E. hirta extracts with high phenolic and flavonoid contents can work together to reduce oxidative stress and protect the body from a variety of diseases.